HUBUNGAN POSISI DUDUK DAN LAMA DUDUK TERHADAP KEJADIAN LOW BACK PAIN PADA PEKERJA SEKTOR INDUSTRI: SEBUAH TINJAUAN SISTEMATIS - Murti Latifah (2022)
Background: Low back pain (LBP) is an ergonomic problem that is often found in the implementation of occupational health that can lead to decreased worker productivity. Low Back Pain (LBP) includes musculoskeletal disorders caused by incorrect posture while working and static posture. Objective: To determine the correlation of sitting position and sitting time with low back pain (LBP) among industrial sector workers. Method: Uses the systematic review method with the PRISMA protocol. Journal articles published between 2011-2021 on the Google Scholar and PubMed database, use Indonesian or English. Articles that meet inclusion criteria are conducted quality test using JBI Critical Appraisal Tools. Results: Obtained 29 journal articles with characteristics of articles that discuss sitting position (10/29), sitting time (7/29) and both (12/29). The number of samples in the study ranged from 20-387 people and most used cross-sectional research designs. Workers tend to work in a sitting position that is not ergonomic so they experience LBP. The length of a worker's sitting varies from <1 hour to 10 hours per day. Sitting position is statistically related to LBP (20/29). Sitting time is statistically related to LBP (17/29). Conclusion: Incorrect sitting positions maintained for a long-time risk causing LBP complaints.